Asthma screening of inner city and urban elementary school-aged children. (December 2013) - Amin, Priyal; Levin, Linda; Smith, Andrew; Davis, Benjamin; Nabors, Laura; Bernstein, Jonathan A.
Abstract Objective: Currently, in the United States there is a lack of a standardized method to effectively screen school children with undiagnosed or poorly controlled asthma. The purpose of this proof-of-concept study was to assess the use of the American College of Allergy, Asthma, and Immunology's (ACAAI) Asthma Screening Questionnaire to identify elementary school-age children at risk for asthma (undiagnosed) or poorly controlled asthma. Methods: Children in grades 3–5 from one urban and two suburban schools completed ACAAI's 14 question asthma screening questionnaire and had their peak expiratory flow (PEF) measured. Children were considered to have a positive asthma screen and be at risk for having undiagnosed or poorly controlled asthma if they answered 'yes' to more than three questions. Children were referred to a physician if they had a positive asthma screen, a previous history of asthma, or a low PEF. Results: Of the 86 participants, 52 were identified as being at risk for asthma. The number was higher among children attending an urban versus suburban school (p = 0.04). The sensitivity and specificity of the screening questionnaire for identifying asthma risk were 90% and 66%, respectively, when the number of 'yes' responses for a positive screen was increased from three to five of 14 questions. Conclusions: The ACAAI's Asthma Screening Questionnaire identified 52 children at risk for undiagnosed or poorly controlled asthma. Our findings support the need to validate this questionnaire to be used in conjunction with PEFR for identifying elementary school children at risk for asthma.